The Effect of ASIC3 Knockout on Corticostriatal Circuit and Mouse Self-grooming Behavior - Wu, Wei-Li; Cheng, Sin-Jhong; Lin, Shing-Hong; Chuang, Yu-Chia; Huang, Eagle Yi-Kung; Chen, Chih-Cheng (Frontiers in Cellular Neuroscience, 2019)
Stereotypic and/or repetitive behavior is one of the major symptoms of autism spectrum disorder (ASD). Increase of self-grooming behavior is a behavioral phenotype commonly observed in the mouse models for ASD. Previously, we have shown that knockout of acid-sensing ion channel 3 (ASIC3) led to the increasd self-grooming behavior in resident-intruder test. Given the facts that ASIC3 is mainly expressed in the peripheral dorsal root ganglion (DRG) and conditional knockpout of ASIC3 in the proprioceptors induced proprioception deficits. We speculate a hypothesis that stereotypic phenotype related to ASD, pareralled with striatal dysfunction, might be caused by proprioception defect in the peripheral sensory neuron origin. Herein, we investigate in depth whether and how ASIC3 is involved in the regulation of self-grooming behavior. First, we observed that Asic3 null mutant mice exhibited increased self-grooming in social interaction during juvenile stage. Similarly, they displayed increased self-grooming behavior in a novel cage in the absence of cagemate. To further understand the mechanism by which ASIC3 affects grooming behavior, we analyzed neurochemical, neuropathological and electrophysiological features in the dorsal striatum of Asic3 null mutant mice. Knockout of Asic3 increased dopamine activity and phospho-ERK immunoreactivities in the dorsal striatum. Furthermore, we detected a lower paired-pulse ratio and impaired long-term potentiation in corticostriatal circuits in Asic3 null mutant mice as compared with wild-type littermates. Moreover, Asic3 knockout altered the medial spiny neurons in the striatum with defects in presynaptic function and decrease of dendritic spines. Lastly, genetic ablation of Asic3 specifically in parvalbumin-positive cells resulted in the increase of self-grooming behavior in mice. These findings suggest ASIC3 knocout in the parvalbumin+ neurons alter grooming behavior by co-opting corticostriatal circuits.